Reviews (Blackfriars, 1961)
Book reviewed in this article: Vatican Diplomacy. By Robert Graham, s.j. Race and Nationalism. The struggle for power in Rhodesia-Nyasaland. By Thomas M. Franck, with a Foreword by James Callaghan, m.p. Some Reflections on Genius and other essays. By Russell Brain. Mémoires Intérieurs. By François Mauriac. Christian Faith and Greek Philosophy. By A. H. Armstrong and R. A. Markus. T. S Eliot and the Idea of Tradition. By Sean Lucy.